Orthoepic nature of the statement of facts in the response component of the dialogue (on the material of the Yakut Language) - Egorovich Alekseev, Ivan; Nikolaevna Sorova, Irina (Universidad del Zulia, 2019)
This article analyzes the main structural-semantic and functional-intonational features of the response phrase in the Yakut language. Typical dialogical constructions with a statement of facts, interacting with interrogative components of the dialogue, are determined from the actual linguistic material with intellectual and communicative content.